Exploratory Assessment of the Factors of Personality Trait of Mathematics Teacher’s that Effects on the Academic Achievements: A Statistical Surveyed Approach - Devi, Shila; Wahab, Zaira; Siddiqui, Afaq Ahmed (Journal of Basic & Applied Sciences, 2017)
The interaction between teachers and students is one of the aspect that helps the students in their career grooming because teacher's personality and their behavior is responsible for his/her effectiveness in the teaching and plays an important role in learning process in terms of achievement and success in the classroom as well as in their entire life. It has been proved that the personality factors such as extraversion, conscientiousness, openness to experience, neuroticism and agreeableness are the key characteristics of teachers’ personality and behavior. The aim of this study is to investigate the effect of teachers’ personality on students’ academic achievement particularly in mathematics subject. In order to pursue the objectives of the study, researcher used quantitative paradigm. Researcher adopted the survey research design for collection of quantitative data. In this way, Big Five Inventory (BFI) is used to identify the teacher’s personality type. This inventory comprised of forty statements about big five personality traits (eight statements about each personality trait). Moreover, the quantitative data is also collected from students’ midterm examination results from the chosen schools. A total of fifty seven public schools and forty five private schools were selected through stratified random sampling technique. The participants of the study comprised of public and private sector elementary 6th -8thgrade school teachers of Karachi, Pakistan. The reliability of the data is found to be around 0.7 of each construct in both sets of data. An independent t test was used to analyze the difference in responses of public and private school teachers. The significance value (P-value) of this indicates that there is statistically significant difference among responses of public and private school teacher’s responses regarding their personality styles that affect the academic achievement of the students. Furthermore, for an inside study a multivariate statistical tool “Exploratory Factor Analysis (EFA)” was used to explore and identify the most important factor in the data. Finally, four factors emerged in the data. The factors emerged in both of sets of data indicates that combination of Agreeable and Conscientious are the most important personality style of teachers that may affect the academic achievement of students.